Machinability Study Of Porous Sea Coral Material For Use In Bone Grafting - Japar, Mohd Anuar (Universiti Sains Malaysia, 2004)
Research of Sea coral as bone substitute has been reported in many experimental studies. It has been proven to be biocompatible. However the implementation of the material may be limited if the material cannot be processed into a shape required to perform its function. This project presents an investigation into machinability of Dead Sea coral from Porites sp. The experimental work is based on Taguchi orthogonal array for optimizing surface integrity by investigating three machining parameters feed rate, depth of cut and spindle speed besides the assessment on cutting too wear and chip fragment.